Effect of Compensation and Work Environment on Employee Performance in Palm Oil Plantation Sector Companies in Riau - Inayah, Fitra; Nugroho, Gilang (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This study aims to analyze the effect of Compensation and Work Environment on Employee Job Satisfaction in Palm Oil Plantation Sector Companies in Riau. The object of this research is the Palm Oil Plantation Sector Companies in Riau Province with a sample of 150 respondents. Data analysis techniques using Structural Equation Modeling using Smart PLS version 3 application. The findings of this study indicate that compensation has a positive and significant effect on employee performance in Palm Oil Plantation Sector Companies in Riau. Meanwhile, the work environment does not have a significant effect on performance. Based on the determination test, it is concluded that compensation and work environment simultaneously affect employee performance in Palm Oil Plantation Sector Companies in Riau.